2020
DOI: 10.1038/s41556-020-00595-5
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA H19 alleviates muscular dystrophy by stabilizing dystrophin

Abstract: Dystrophin proteomic regulation in Muscular Dystrophies (MD) remains unclear. We report that a long noncoding RNA (lncRNA), H19 , associates with dystrophin and inhibits E3 ligase-dependent poly-ubiquitination at Lys3584 (referred to as Ub-DMD) and its subsequent protein degradation. In-frame deletions in BMD and a DMD non-silent mutation (C3340Y) result in defects in the protein’s ability to interact with H19 , causing elevated Ub-DMD levels and dystrophin degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 63 publications
(48 reference statements)
0
48
0
Order By: Relevance
“…Among these non-coding RNAs, microRNAs have been sufficiently demonstrated by us and others to exert critical regulatory roles in various cancers (Yuan et al, 2011;Chang et al, 2014Chang et al, , 2017. Long non-coding RNAs (lncRNAs) are another class of noncoding RNAs with more than 200 nucleotides in length (Ponting et al, 2009;Zhang Y. et al, 2020). lncRNAs have been gradually revealed to exhibit regulatory roles in a variety of cancers (Schmitt and Chang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among these non-coding RNAs, microRNAs have been sufficiently demonstrated by us and others to exert critical regulatory roles in various cancers (Yuan et al, 2011;Chang et al, 2014Chang et al, , 2017. Long non-coding RNAs (lncRNAs) are another class of noncoding RNAs with more than 200 nucleotides in length (Ponting et al, 2009;Zhang Y. et al, 2020). lncRNAs have been gradually revealed to exhibit regulatory roles in a variety of cancers (Schmitt and Chang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies using different cell types support that H19 is mainly, even exclusively, expressed in the cytoplasm 43 45 . Based on this subcellular location, competing endogenous RNA regulation is the most reported mechanism of action of H19, followed by direct binding to transcription regulators or other proteins 46 , 47 . Currently, few study have investigated the role of H19 in regulating mRNA translation.…”
Section: Discussionmentioning
confidence: 99%
“…H19 was also shown to play an important role in various cardiovascular diseases such as acute myocardial infarction (Huang et al 2020 ), myocardial I/RI (Li et al 2019a , b ) and cardiomyocyte hypertrophy (Viereck et al 2020 ). It has also been confirmed that H19 plays a noticeable role in embryonic placental growth, skeletal muscle differentiation and related diseases (Dey et al 2014 ; Zhang et al 2020 ).…”
Section: Introductionmentioning
confidence: 88%